2021
DOI: 10.1016/s0140-6736(21)00441-4
|View full text |Cite|
|
Sign up to set email alerts
|

Patient care and clinical outcomes for patients with COVID-19 infection admitted to African high-care or intensive care units (ACCCOS): a multicentre, prospective, observational cohort study

Abstract: Background There have been insufficient data for African patients with COVID-19 who are critically ill. The African COVID-19 Critical Care Outcomes Study (ACCCOS) aimed to determine which resources, comorbidities, and critical care interventions are associated with mortality in this patient population.Methods The ACCCOS study was a multicentre, prospective, observational cohort study in adults (aged 18 years or older) with suspected or confirmed COVID-19 infection who were referred to intensive care or high-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
128
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 27 publications
13
128
5
Order By: Relevance
“…Other reasons may feature more prominently in LMICs. For example, reported COVID-19 cases and deaths have been consistently lower in most LMICs relative to higher-income countries 16 18 . If individuals feel the risk of disease is less severe, they may be less willing to accept any perceived risks of vaccination 19 .…”
Section: Mainmentioning
confidence: 99%
“…Other reasons may feature more prominently in LMICs. For example, reported COVID-19 cases and deaths have been consistently lower in most LMICs relative to higher-income countries 16 18 . If individuals feel the risk of disease is less severe, they may be less willing to accept any perceived risks of vaccination 19 .…”
Section: Mainmentioning
confidence: 99%
“…Nevertheless, rapid mortality assessments for COVID-19 that is underway in some countries [35][36][37][38] could reveal a more complete picture. Expectedly, due to weak health systems, recent data show that Africa has a higher mortality in those with critical COVID-19 illness than elsewhere, with a mortality rate of 48.2% compared with a global average of 31.5% [39].…”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to the burden of underlying comorbidities and resource deficits. 8 Reports globally have indicated that increasing age, [9][10][11] comorbidities (cardiovascular disease, diabetes) 9,12,13 and obesity 14,15 are all associated with adverse outcomes. In addition, certain demographic characteristics [10][11][12]16 and laboratory parameters [17][18][19] have also been associated with the severe form of COVID-19 and increased mortality.…”
Section: Introductionmentioning
confidence: 99%